Influência da idade de doadoras humanas sobre a estabilidade de seus eritrócitos - Firmino, Cynthia Barbosa (2007)
Chapter II - [Introduction] The stability of a biological membrane is resultant from its composition and from the composition of the internal medium of the living organism, which depends on genetic influences, feeding and life style. [Objective] This work aimed to study transversally in a human female population the dependence of the erythrocytes stability with age, nutritional status, erythrocytes counting and medium corpuscular volume (MCV). [Subjects] The sample was constituted of human females (N = 67), with 20 to 94 years, proceeding from a defined region with similar dietary habits and life styles. [Methods] The erythrocytes stability against hypotonic lysis and ethanol action was given by the concentration of NaCl (H50) or ethanol (D50) capable to promote 50% of hemolysis. The H50 values were determined at 26, 32, 37, 42 and 47 °C; the D50 values were determined only at 37 °C. The nutritional status of the volunteers was evaluated with the Mini-Nutritional Assessment (MNA). [Results] H50 was inversely dependent (P<0.05) with age and MCV, but not with MNA score neither the erythrocyte counting of the volunteer, at 26, 32, 37 and 42 °C, but not at 47 °C. D50 presented a linear and positive dependency with the volunteer age. H50 present a linear and negative dependence with the temperature increase. The H50 values in the thermal dependence line of H50 for the females with 20 to 39 years were significantly higher than those for the females above 60 years. [Conclusions] The stability of the erythrocytes against hypotonic stress and denaturation by ethanol increased with the age of the volunteers. This stability increase was not determined by differences in the nutritional status neither in medium corpuscular volume. The stability of the erythrocytes decreased significantly with the temperature increase between 26 and 47 °C. The females above 60 years presented erythrocytes with higher stability than the females with 20 to 39 years within this thermal interval.